Assessment of body image in patients with obesity and binge eating disorder - Kjersti Hognes Berg; Charlotte Fiskum; Trine Tetlie Eik-Nes (Fysioterapeuten, 2021)
Introduction: The paper describes a model for assessing body image in patients with obesity and binge eating disorder. The aim is to contribute to the physiotherapeutic body of knowledge concerning bigger bodies. The paper is rooted in a pilot project conducted at Nord-Trøndelag Hospital Trust.